Penghitungan Volumetrik Perdarahan dengan Metode Volume Automatik (Software Volume Evaluation) dan Metode Manual (Broderick) pada MSCT Kepala (Study Eksperimen pada Pasien Perdarahan Intraserebral di RS. Haji Surabaya) - Agus Setyo Kiswoyo; Gatot Murti Wibowo; Widiana Ferriastuti (Poltekkes Kemenkes Semarang, 2017)
Background : Intracerebral hemorrhage (ICH) is the brain parenchyma bleeding. The volume of intracerebral hemorrhage can affect mild to severe clinical symptoms due to increased intracranial pressure and it has a high risk of death. In addition, CT scan CTScan is a gold standard on PIS examination. Methods : This was a quantitative research with experimental approach. There are two methods of volumetric hemorrhage calculation, namely automatic and manual method. Automatic Volume Method (SVE) is a volume calculation by computer software available on CT Scan tool with voxel calculation in HU value range. The manual method (Broderick) used is AXBXC/2 which is the multiplication of length (A), width (B) and height/thickness of bleeding slice (C) divided by 2. From the result, the volume differencewas tabulated and measured, then the normality and different test were done.Results : The sample consisted of 10 new bleeding patient data which then classified into small hemorrhage group, calculated volumes automatic(SVE) and manual(Broderick). volume calculations obtained different values of volume ranging from 0.37 cm³ to 10.01 cm³, the percentage ranged from 3% to 41%. The result showed a very significant difference value due to the different test Paired Samples T Test with significance value of 0.001 (p-Value 0.05). From the data, 8 patients with different percentage above 20%,with average 25% were PIS with irregular shape. And 2 patients with volume difference below 10% with average 6 % were Intracerebral Hemorrhage regular shape. Conclussions : There is a difference in the calculation of volumetric Intracerebral hemorrhage between the automatic volume method (SVE) and the manual method (Broderick). With a percentage average difference of average volume of 6% for regular shapes and 25% for irregular hemorrhage.